Indonesia's Response to the Rise of Anti-Asian Hate Racial Discrimination in the United States in 2020-2021 in a Human Security Perspective - IYANDRAPUTRA, YOSIA OCTAFREIRA; Sidik, Hasan; Yulianti, Dina (Padjadjaran Journal of International Relations, 2026)
From the colonial era to the contemporary period, the history of the United States (US) has recorded many cases of racism, although in the 20th century  the Civil Rights Movement ended legal segregation. Cases of racism strengthened again in 2020–2021 targeting Asians in the US, including Indonesian citizens, after Covid-19 was referred to as the "China virus" by President Trump. This study aims to describe the response and efforts made by the Indonesian government in dealing with the increasing cases of racial violence against Asians that threaten the security of Indonesian citizens in the US, from the perspective of human security The methods used in this study are qualitative with interview techniques, literature studies, and internet-based research. Indonesia's efforts to address the security of Indonesian citizens in the United States include establishing communication with the diaspora community and students through online meetings, as well as building cooperation with US security authorities, ranging from local police units to FBI representatives. Sejak era kolonial hingga masa kontemporer, sejarah Amerika Serikat (AS) mencatat sangat banyak kasus rasisme, meski pada abad ke-20 Civil Rights Movement mengakhiri segregasi hukum. Kasus rasisme kembali menguat pada 2020–2021 yang menyasar warga Asia di AS, termasuk WNI, setelah Covid-19 disebut sebagai “virus China” oleh Presiden Trump. Penelitian ini bertujuan untuk mendeskripsikan respons dan upaya yang dilakukan pemerintah Indonesia dalam menghadapi meningkatnya kasus kekerasan rasial terhadap orang-orang Asia yang mengancam keamanan WNI di AS, dalam perspektif keamanan manusia Metode yang digunakan dalam penelitian ini adalah kualitatif dengan teknik wawancara, studi pustaka, dan penelitian berbasis internet. Upaya Indonesia dalam menangani keamanan WNI di Amerika Serikat antara lain dengan menjalin komunikasi dengan komunitas diaspora dan mahasiswa melalui pertemuan online, serta membangun kerjasama dengan otoritas keamanan AS, mulai dari satuan kepolisian setempat hingga perwakilan FBI.